Pengembangan Game Edukasi Matematika Geometri Untuk Siswa Kelas V Sekolah Dasar Kristen Ngampin - Agus Priyadi; Ahmad Zainudin; Eko Rustanto (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2022)
Mathematic Geometry Educational Game Development for Fifth Grade Students at SD Kristen Ngampin. Educational game is a game which is specifically designed as a tool to accomplish educational needs. Therefore, it has to be projected in an exact precision to achieve its goal: educating, and increasing the user knowledge and skills. There are some problems which frequently happened at SD Kristen Ngampin, especially for fifth grade students, related to the media game utilization in learning. Firstly, conservative learning which is already applied by the teacher, lead them to have less curiosity in learning the material. Secondly, the media learning limitation affects the students’ independence learning and their participation on the learning process. The software used in this game development was Adobe Flash CS6. The research was conducted through R&D; Research and Development method by processed through some stages. First, problem identification stage, then, data collection, product design, design validation, design revision, and the final step was the product trials. The validation was carried out by the expert validators and product user. Based on the research conducted, it concluded that educational game enhances insight and direct experience about Mathematic learning, especially on geometry material for fifth grade students of SD Kristen Ngampin.